1998
DOI: 10.1002/(sici)1097-4652(199810)177:1<137::aid-jcp15>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell apoptosis, lymphocyte recruitment and tumor vascular changes are induced by low temperature, long duration (fever-like) whole body hyperthermia

Abstract: A single treatment of low-temperature, long-duration, whole-body hyperthermia of either severe combined immunodeficient (SCID) mice bearing human breast tumor xenografts or Balb/c mice bearing syngeneic tumors for 6-8 hr can cause a temporary reduction of tumor volume and/or a growth delay. In both animal model systems, this inhibition is correlated with the appearance of large numbers of apoptotic tumor cells. Because this type of mild heat exposure, comparable to a common fever, is not itself directly cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(83 citation statements)
references
References 43 publications
6
77
0
Order By: Relevance
“…16,21) In fact, caspase-3 and caspase-7 share similar substrate specificity, 22) and the induction of apoptosis by anti-cancer agents through the activation of caspase-7 independent of caspase-3 has been documented. 23) The limitation of conventional approach for hyperthermia is the uneven thermal effect, 10,15) for thermal energy was conducted from a heat source, and therefore the healing effect maybe different depended on the distance from the heat source. one of the advantages of microwave heating used in the present study is a precise manipulation of temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,21) In fact, caspase-3 and caspase-7 share similar substrate specificity, 22) and the induction of apoptosis by anti-cancer agents through the activation of caspase-7 independent of caspase-3 has been documented. 23) The limitation of conventional approach for hyperthermia is the uneven thermal effect, 10,15) for thermal energy was conducted from a heat source, and therefore the healing effect maybe different depended on the distance from the heat source. one of the advantages of microwave heating used in the present study is a precise manipulation of temperature.…”
Section: Discussionmentioning
confidence: 99%
“…10) In addition to a direct effect, the enhancement of the cytotoxicity of chemotherapeutic agents at around 41°C has also been well characterized. 11,12) The purpose of the present study was to determine the effects of short-term hyperthermia at 41°C for 2 h on PTX-induced anti-tumor activity using human breast cancer MCF-7 cells.…”
Section: Short-term Hyperthermia Promotes the Sensitivity Of Mcf-7 Humentioning
confidence: 99%
“…At the cellular level, it has been shown that fever-like treatments of lymphocytes (39.5°C for 6 -8 h) leads to activation of protein kinase C, massive cytoskeleton changes characteristic of a heightened activation status, and the induction of hsps including hsc70 and hsp110 (22, 48 -49). In mice, fever-level hyperthermia has been shown to lead to an antitumor effect involving both the innate and specific immune systems (50). It is possible that mild hyperthermia, which is nontoxic, may lead to several changes in immunological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be determined if hyperthermia can exploit IL-6 and the soluble IL-6 receptor in the tumor microenvironment to improve vascular adhesion similar to that observed in HEVs. In addition to changes in tumor blood flow and oxygenation associated with hyperthermia [44], improved vascular adhesion may theoretically enhance T lymphocyte infiltration into tumor sites, as has been reported for natural killer lymphocytes [22]. T lymphocyte infiltration is critical to antitumor responses and improved patient survival [45][46][47].…”
Section: Clinical Implications Of Thermal Therapy Dynamicsmentioning
confidence: 94%
“…As a nontoxic treatment, whole-body hyperthermia (WBH) maintains an elevation of core body temperature by isolating an organism in a contained, temperaturecontrolled environment, thereby mimicking the thermal component of fever [12,21,22]. As previously stated, elevated core body temperatures in the febrile range have been associated with improved survival in homeotherms and poikilotherms; however, alterations in the immune system during thermal stress were largely undefined.…”
Section: Enhanced Lymphocyte-endothelial Interactions With Hyperthermiamentioning
confidence: 99%